An Exploratory Assessment of Health Screening and Referral Services under the Rashtriya Bal Swasthya Karyakram (RBSK) in Tumkur District, Karnataka - Lahari M N,Priyanka Tiwari (International Journal of Advanced Research and Multidisciplinary Trends (IJARMT), 2025)
The Rashtriya Bal Swasthya Karyakram (RBSK) is a flagship initiative under the National Health Mission aimed at early identification and intervention for children from birth to 18 years across four broad categories: defects at birth, diseases, deficiencies, and developmental delays including disabilities. This exploratory study assesses the effectiveness of health screening and referral services under RBSK in the Tumkur district of Karnataka. Using a qualitative approach, the study gathered data through in-depth interviews, focus group discussions, and a review of program records. The findings reveal that while RBSK has successfully enabled the early identification of several health issues among children, its implementation is hampered by challenges such as limited awareness among beneficiaries, referral bottlenecks, inadequate transport facilities, and staffing constraints. Strengthening community outreach, improving referral mechanisms, and capacity-building of Mobile Health Teams (MHTs) are essential to enhance the program’s impact. The study concludes with practical recommendations for improving the overall efficiency and outreach of RBSK in rural districts like Tumkur.